(untitled) - Furuta, Ryoichi (Tokyo, 1967)
Contents: The earliest times; the nara period (and proximate years); the heian period; the kamakura period; the period of the northern and southern courts; the muromachi period; the azuchi-momoyama period; a general survey of the yedo period; shipping between yedo and the home provinces; the eastabout passage; the westabout passage; meiji & taisho; the showa period: part 1; the showa period: part 2, translator's note...
Keywords: Hàng hải,Shipping; Lịch sử,History; Nhật Bản,Japan